Tonga : 2009 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Tonga. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Tonga's growth is likely to be low in the near term as remittances remain constrained by global economic conditions. The staff report for Tonga's 2009 Article IV Consultation highlights economic developments and policies. The reconstruction of the central business district and increased subsistence agriculture are likely to cushion the downward pressures. Risks are, however, tilted to the downside, mainly owing to increasing unemployment in remittance-sending economies and rising oil prices. The drawdown of the large reconstruction loan will lead to high risk debt levels over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet